Genetic variability and heritability in tomato (Lycopersicon esculentum) genotypes during summer season under plastic-house condition - PHOOKAN, DEEPA BORBORA; TALUKDAR, P; SHADEQUE, A; CHAKRAVARTY, B K (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1991-92 at jorhat to evaluate 29 genotypes of tomato (Lycopersicon esculentum Mill.) in relation to 8 different growth and yield-attributing parameters under plastic-house condition during summer season. ’Vaishali’ tomato recorded the maximum yield of 1.60 kg/plant followed by 1.34 kg/plant in the genotype ’Sutton Gram Prolific’. All the characters except branch number were found to be highly heritable. High genotypic and phenotypic coefficient of variation, heritability and genetic advance as percentage of mean were estimated for fruits/ plant, fruit-setting percentage and average fruit-weight suggesting their importance in the selection programme of tomato improvement.